2015
DOI: 10.17576/jsm-2015-4402-16
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Drying Methods on the Antioxidant Activities of Leaves and Berries of Cayratia trifolia

Abstract: This study aimed to assess the effects of fresh, thermal drying method (vacuum oven drying), and nonthermal drying method (freeze drying) on the antioxidant activities of leaves and berries of Kajian ini bertujuan menilai kesan kaedah pengeringan yang berbeza terhadap sampel segar, kaedah pengeringan terma (pengeringan ketuhar vakum) dan kaedah pengeringan tak terma (pengeringan beku) ke atas aktiviti antioksida daun dan beri Cayratia trifolia yang diukur melalui asai kuasa antioksidan penurunan ferik (FRAP) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 18 publications
(24 reference statements)
3
16
1
2
Order By: Relevance
“…In general, the content of flavonoids content in ovendried samples was higher than that in the freeze-dried samples. These results are not in concordance with those obtained by Rabeta and Lin (2015) [42] who studied the same drying methods on antioxidant activities (including flavonoids) of leaves and berries of Cayratia trifolia.…”
Section: Resultscontrasting
confidence: 90%
“…In general, the content of flavonoids content in ovendried samples was higher than that in the freeze-dried samples. These results are not in concordance with those obtained by Rabeta and Lin (2015) [42] who studied the same drying methods on antioxidant activities (including flavonoids) of leaves and berries of Cayratia trifolia.…”
Section: Resultscontrasting
confidence: 90%
“…The same finding was reported by Wong et al (2010); they indicated that freeze-dried samples of Alpinia species leaves can preserve antioxidant properties. Freeze-drying sample of leaves and berries of Cayratia trifolia or lakom also yields the highest antioxidant activity among vacuum-oven dried samples (Rabeta and Lin, 2015).…”
Section: Antioxidant Activity Assays (Dpph and Frap)mentioning
confidence: 93%
“…Dilution effects may be the reason for the low antioxidant activity, TPC, and total flavonoid content (TFC) of compounds. This low performance was attributed that the enzymes in fresh leaves were still active, and they can lead to enzymatic degradation (Rabeta and Lin, 2015). High moisture content in fresh samples can be an indicator of high water activity.…”
Section: Total Phenolic Content (Tpc)mentioning
confidence: 99%
“…For this step, plant samples are usually freeze dried. It has been reported that non-thermally dried plants (lyophilization) result in higher flavonoids detection compared to thermal drying or fresh samples [87].…”
Section: Extraction Of Plant Flavonolsmentioning
confidence: 99%
“…Ramps were cleaned and stored in a -20 o C freezer until used for analysis. Ramps samples were lyophilized and pulverized for analysis because it was reported that this technique maximizes flavonols extraction [87].…”
Section: Plant Materialsmentioning
confidence: 99%